Motivations Of Farm Stay Hosts And Guests: A Phenomenological Study ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Studies pertaining farm tourism chiefly highlights positivistic methodologies and quantitative approaches.  However, there is need to explore, describe and better understand the intricacies of tourism impacting the farm, the families and  rural surroundings. Interpretative research methods are comprehensive and ease off compound understanding of human  dynamics involved in farm tourism. This phenomenological study explores the farm tourism experiences in Shimla from the  perspective of both hosts and guests. Objective:The aim of the study was to understand different motivations people have to run  a farm tourism business, and what motivates visitors to seek holidays at these destinations. Methodology: The personal  narratives of hosts interviewed clarified assumptions about the motives for embracing farm tourism, the most significant being  meeting new people. Results: Findings suggest that tourists were motivated with the desire to unwind in the serene rural  landscape and to learn about rural lifestyle infused with culture and Horti practices. Incidentally, the stimulus for both the  classes were found to be highly coherent with each other indicating bright future of farm stay tourism in the region. Conclusion: Both guest and host motivations were found to be compatible indicating a prospective future for farm tourism.
Keywords: Farm Tourism; Positivistic; Horticulture; Interpretative; Phenomenological